The social responsibilities in companies and its effects of applying the sustainable development during (2013-2018) -Case Study-Foreign oil companies in Basra province - فارس شهيل شداد; عبد الحسين عدنان فرحان (Journal of Petroleum Research and Studies, 2023)
The purpose of the search impact of social responsibility (SR) on indicators of (SD) in Basra Governorate will be highlighted to promote a new concept or another challenge to be added to the set of (SD) challenges in Iraq in general and Basra in particular, as the importance of social responsibility must be enhanced in various economic activities to achieve integration between society and the economy, which It will certainly cast a shadow over development and its requirement.